2012
DOI: 10.1017/s1368980012005216
|View full text |Cite
|
Sign up to set email alerts
|

A content analysis of food advertisements appearing in parenting magazines

Abstract: Objective: Childhood obesity is a growing problem in the USA. As parents play a major role in shaping a child's diet, the present study examines food advertisements (ads) directed towards parents in parenting and family magazines. Design: Given the potential for magazines to influence attitudes and knowledge, we used content analysis to examine the food ads appearing in four issues each of six different parenting and family magazines from 2008 (n 24). Setting: USA. Subjects: Food ads in parenting and family ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…The search terms were selected based on our review of existing native ads and the recommended/avoided labels from FTC guidelines. Overall methodology is based on the review of online news analysis in previous studies (Habel, Liddon, and Stryker 2009;Heuer, McClure, and Puhl 2011;Manganello et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The search terms were selected based on our review of existing native ads and the recommended/avoided labels from FTC guidelines. Overall methodology is based on the review of online news analysis in previous studies (Habel, Liddon, and Stryker 2009;Heuer, McClure, and Puhl 2011;Manganello et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…We also used prior work on magazine advertising of food products 21 and alcohol 22 as well as published literature on alcohol advertising 23 to draft an initial coding framework. In addition to coding for whether each ad contravened any federal regulation or industry standard, we coded for the existence, content, and prominence of a tagline and a responsibility message.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have examined the promotion of children's foods and beverages directly to parents. Previous studies have examined the promotion of children's foods and beverages in parenting 9,10 or general adult 11 magazines and have described case studies of children's products promoted to parents. 12,13 One study of a random sample of 100 Australian television advertisements for children's foods aired in 2009 14 reported that 24% of advertisements were considered emotionally appealing to parents, in that they included themes of family life or a parent's concern for their child's wellbeing or health.…”
Section: What This Study Addsmentioning
confidence: 99%